Development of simple and biodegradable pH indicator films from cellulose and anthocyanin - Fikrte Woldeyes Hailu; Solomon Workneh Fanta; Alemayehu Ambaw Tsige; Mulugeta Admasu Delele (Discover Sustainability)
Abstract This study developed intelligent packaging applications by combining anthocyanin extracts from butterfly pea flowers (BP, at initial pH, and BP7, at pH 7) and red cabbage (RC, at initial pH) with a cellulose-chitosan matrix. Mechanical, physical, microstructural, and pH-sensitive properties of the BP7, BP, RC, and control (anthocyanin-free) indicator films were examined. The results showed that the BP film indicator had a distinct colorimetric response compared to RC and BP7 films. This is because the butterfly pea anthocyanin, which has a unique capacity to react with different pH buffer solutions, was used to form the BP film. The highest film thickness value of 208.67 ± 0.58 µm and tensile strength value of 14.0 ± 0.05 MPa were recorded from the BP film. The microstructural results also showed a uniform anthocyanin distribution over the biopolymer matrix, as seen in the BP indicator film. However, other film parameters, such as moisture content and solubility for all anthocyanin-containing films, showed lower values (< 14% and < 7%, respectively) compared to the control film (18.96 ± 0.43% and 21.80 ± 1.51%, respectively). The control film showed higher moisture and solubility, which can be attributed to the fact that chitosan is very hydrophilic in the film matrix. Nevertheless, the anthocyanin-developed films displayed a decrease when the anthocyanin hydroxyl chemical groups formed more hydrogen bonds with the water and the biopolymer matrix. The findings showed that overall; the colorimetric film indicator for the BP film was superior. These could be employed in the food packaging sector as intelligent packaging film indicators to track the freshness of products.